2015
DOI: 10.1055/s-0035-1561277
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Investigation of the Antitumor Properties of Novel, Bicyclic Furopyrimidine, Pyrrolopyrimidine and Pyrimidopyridazine Nucleoside Analogues

Abstract: A series of nine hitherto unknown bicyclic pyrimidine nucleoside analogues (BCNAs) bearing bicyclic furo[2,3-d]pyrimidin-2(3H)one, 3H-pyrrolo[2,3-d]pyrimidin-2(7H)-one and 5,6-dihydropyrimido[4,5-c]pyridazin-7(8H)-one bases were prepared in a straightforward approach. Each of the synthesized compounds possesses a β-D-ribofuranose, β-D-2-deoxyribofuranose or β-D-arabinofuranose moiety attached to the heterocyclic ring system. This is one of few examples of the synthesis of pyrrolo[2,3-d]pyrimidin-2(7H)-one and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Compound 1 has a strong structural relationship to pyrrolo-dC (2) and imidazolo-dC (3) (see Scheme 1), and is decorated with a phenyl ring, as is the case for 2 and 3 (Hudson & Ghorbani-Choghamarani, 2007;Mei et al, 2014). A 3-methylpyrimido[4,5-c]pyridazine nucleoside (Loakes et al, 2003a,b) and a phenylethyl derivative were reported previously (Mieczkowski et al, 2016). Nucleoside 1 was synthesized in our laboratory and incorporated into DNA oligonucleotides employing phosphoramidite chemistry and solid-phase oligonucleotide synthesis (Mei et al, 2015).…”
Section: Introductionmentioning
confidence: 79%
“…Compound 1 has a strong structural relationship to pyrrolo-dC (2) and imidazolo-dC (3) (see Scheme 1), and is decorated with a phenyl ring, as is the case for 2 and 3 (Hudson & Ghorbani-Choghamarani, 2007;Mei et al, 2014). A 3-methylpyrimido[4,5-c]pyridazine nucleoside (Loakes et al, 2003a,b) and a phenylethyl derivative were reported previously (Mieczkowski et al, 2016). Nucleoside 1 was synthesized in our laboratory and incorporated into DNA oligonucleotides employing phosphoramidite chemistry and solid-phase oligonucleotide synthesis (Mei et al, 2015).…”
Section: Introductionmentioning
confidence: 79%
“…Despite the persistent synthetic pursuit of furopyrimidine nucleosides, so far only a few and only C-6 substituted have been crystallographically characterized. 20 , 25 , 38 , 40 , 42) , 43) , 44) , 45) , 46) Although nucleosides are often resistant to crystallization, efforts to obtain diffraction quality crystals were successful for compound 4 , using methanol at room temperature. X-Ray crystallography confirmed the structure of the 3',5'-di- O -acetyl-5-iodo-6-( p -tolyl)furopyrimidine ( 4 , Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…During our research on the design and discovery of novel anticancer compounds based on diverse heterocyclic structures, such as 6 H ‐oxazolo[3,2‐ f ]pyrimidine‐5,7‐dione, 47 1,3,4,12 a ‐tetrahydropyrazino[2,1‐ c ][1,4]benzodiazepine‐6,12(2 H ,11 H )‐dione, 48 as well as nucleoside derivatives 49–52 and natural poliphenolic compounds, 30 we turn our attention to halogenated flavonoid derivatives as possible ligands for tumor‐associated kinase CK2. The compounds used in this study are presented on Figure 1.…”
Section: Resultsmentioning
confidence: 99%